The incorporation of dyes into hair as a model for drug binding - DeLauder, Saundra F.; Kidwell, David A. (Forensic science international, 2000)
The binding of charged substances from external aqueous media to hair has been investigated through the use of fluorescence microscopy. Eleven hair samples, reflecting various ethnic groups and cosmetic treatments, were tested. Rhodamine 6G, a cationic dye representative of drugs such as cocaine and opiates, showed incorporation throughout the hair of all samples except one. In contrast, fluorescein, an anionic dye representative of drugs such as THC carboxylic acid, was not readily incorporated. The incorporation of rhodamine 6G was faster for chemically ‘straightened’ and bleached African–American female hair than for untreated hair. Incorporation of rhodamine 6G followed a pH dependence, but an ionic strength dependence could not be established. These studies support three postulates: (1) electrostatic interactions explain the preferential binding of cationic drugs of abuse to hair; (2) the hair matrix, or the non-helical portion of hair, is accessible to external solutions and thus subject to contamination; and (3) cosmetic treatments may alter the helical portion of hair thereby increasing its accessibility to external contamination.